Automated Analysis of Service Life of Air-Lines of the Electricity Transmission of Electric Power Systems - E. M. Farhadzadeh; A. Z. Muradaliyev; S. A. Abdullayeva; A. A. Nazarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2021)
Basic EPS objects, which service life has exceeded normative value, increasingly affect – every year to a greater extent – the efficiency of overall performance. This manifests itself in increase of a number of automatic emergency shutdowns, an amount and complexities of accident-hazardous defects. After the expiration of the standard service life, there is a special need for a quantitative assessment of reliability and safety of an object. It is recommended to organize the operation, maintenance and repair of these objects according to their technical condition, and since it determines the reliability and safety of the object, these properties should be taken into account more fully. The relevant recommendations in electric power systems are implemented at a qualitative level, intuitively, according to the operating experience. There are neither quantitative evaluations nor methodology for their performance. Therefore, a method and algorithm of quantitative assessment of integral indicators of reliability and safety of operation of thermal power units of thermal power plants as concentrated objects of continuous operation were previously analyzed by the authors. The present paper examines distributed objects of continuous operation, viz. overhead power transmission lines with a voltage of 110 kV and higher, whose service life exceeds the standard value. Attention is paid to the issues of quantitative assessment of the degree of aging for a set of overhead power transmission lines, classification of these lines to identify the most significant classes and methodology for assessing the difference in the degree of aging when classifying them according to specified types of signs (for example, the difference in the degree of aging of overhead power transmission lines of grid enterprises of electric power systems). It is shown that it unacceptable to use the estimates of the relative number of overhead power transmission lines, the service life of which exceeds the calculated one, for comparison since it causes a great risk of an erroneous decision. The methodology and algorithm of methodological support of the management of electric power systems and grid enterprises in the organization of operation, maintenance and repair have been developed.